Floral images of the mythology in the contemporary Ukrainian prose (on the example of the novels by Dara Korniy, Lada Luzina, M. Rialpolova) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The paper investigates the floral images, which constitute the mythworld of modern fantastic prose. The object of research is the works of Ukrainian writers Dara Korney, Lada Lusina and M. Ryapolova. The novel «Gonihmarnik» by Dara Korney is the attempt to adapt the image of the healer woman to the realities of the modern city. In contrast, the cycle «Kyiv witches» by Lada Lusina not only reinterprets the image of a witch who studies plants, but also extends the object on the artifacts. The novel «Buretsvit» by M. Ryapolova is characterized by author's interpretation of the plant world and creation of its own floral elements.
Keywords: interpretation; myth creation; symbol; semantics; fantasy; folklore